Efficacy of ultrasound-guided intensive silver needles in the treatment of shoulder pain - LUO Jia; LIU Jitong; ZHANG Weiwei; LIAO Qian; LIAO Yongqiong (Zhongguo linchuang yanjiu)
Objective To investigate the effects of ultrasound.guided intensive silver needles on the efficacy, pain, shoulder function, inflammatory factors and pain.causing substances in patients with shoulder joint pain. Methods A total of 92 patients with frozen shoulder admitted to Hunan Provincial People..s Hospital from January 2022 to May 2023 were selected, and were divided into two groups with 46 cases in each group by random number table method. The control group received routine electroacupuncture treatment, while the observation group received intensive silver needle therapy under ultrasound guidance, both of which lasted for 4 weeks. After treatment, the clinical efficacy, pain, shoulder joint function, shoulder joint mobility, inflammatory factors, serum pain . causing substances and complications of the two groups were compared. Results The total effective rate of the observation group was 95.65%, which was higher than 82.61% of the control group (χ 2=4.039,P=0.045) . After treatment, the Visual Analogue Scale (VAS) score in both groups were lower compared to before treatment, and that in the observation group was lower compared to the control group; the Japanese Orthopaedic Association (JOA) score and range of motion (ROM) in both groups were higher compared to before treatment, and those in the observation group were higher compared to the control group (P＜0.05) ; the levels of interleukin (IL) -1, IL-8 and tumor necrosis factor α (TNF-α) in both groups were lower compared to before treatment, and those in the observation group were lower compared to the control group (P＜0.05) ; the levels of human serum substance P, neuropeptide Y and nerve growth factor in two groups were lower compared to before treatment, and those in the observation group was lower compared to the control group (P＜0.05) . There was no significant adverse reaction or complication during the treatment period in both groups. Conclusion Compared with conventional electroacupuncture, intensive silver needle guided by ultrasound can effectively improve the efficacy of patients with shoulder joint pain, improve function and ROM of shoulder joint, and reduce the levels of inflammatory factors and serum pain.causing substances, with high safety.